2019
DOI: 10.1177/1550147719879379
|View full text |Cite
|
Sign up to set email alerts
|

Anonymous authentication key agreement scheme with pairing-based cryptography for home-based multi-sensor Internet of Things

Abstract: Home-based multi-sensor Internet of Things, as a typical application of Internet of Things, interconnects a variety of intelligent sensor devices and appliances to provide intelligent services to individuals in a ubiquitous way. As families become more and more intelligent, complex, and technology-dependent, there is less and less need for human intervention. Recently, many security attacks have shown that Internet home-based Internet of Things have become a vulnerable target, leading to personal privacy probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…Wazid et al [20] suggested a lightweight remote user authentication scheme for the smart home environment which fulfills the design criteria for the smart home environment. Yu and Li [21] proposed another user authentication scheme for the smart home environment. However, their protocol did not necessitate a secure environment for user and device registration.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Wazid et al [20] suggested a lightweight remote user authentication scheme for the smart home environment which fulfills the design criteria for the smart home environment. Yu and Li [21] proposed another user authentication scheme for the smart home environment. However, their protocol did not necessitate a secure environment for user and device registration.…”
Section: Related Workmentioning
confidence: 99%
“…In this section, we benchmark the proposed scheme against the schemes proposed by Shuai et al [7], Yu and Li [21], Naoui et al…”
Section: Comparative Studymentioning
confidence: 99%
See 3 more Smart Citations